2001
DOI: 10.1007/s003930170063
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler sonography in the evaluation and follow-up of knee involvement in patients with juvenile idiopathic arthritis

Abstract: This study suggests the Doppler sonography as a non-invasive, low-cost, and readily available tool for the evaluation and follow-up of articular involvement in knees of JIA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…3 In the present study of RA patients, significantly reduced resistance indicated by RI (P Ͻ 0.01) and PI (P Ͻ 0.01) was observed in hypervascular synovium when compared with less vascular synovium. Similarly reduced resistance of synovial vessels in RA patients has been reported by Qvistgaard et al, 3 Shahin et al, 6 and Terslev et al 7,12 In addition, a significant correlation was found between intensity of color flow signals and values of RI (P Ͻ 0.01) or PI (P Ͻ 0.01). From these observations we considered RI or PI to be qualitative indicators in the evaluation of synovial hypervascularity in RA synovium and inflammatory activity of arthritis as well as color flow signals, since the grade of the color flow signals correlated with the grade of synovial effusion as was described in the present study and the previous one.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…3 In the present study of RA patients, significantly reduced resistance indicated by RI (P Ͻ 0.01) and PI (P Ͻ 0.01) was observed in hypervascular synovium when compared with less vascular synovium. Similarly reduced resistance of synovial vessels in RA patients has been reported by Qvistgaard et al, 3 Shahin et al, 6 and Terslev et al 7,12 In addition, a significant correlation was found between intensity of color flow signals and values of RI (P Ͻ 0.01) or PI (P Ͻ 0.01). From these observations we considered RI or PI to be qualitative indicators in the evaluation of synovial hypervascularity in RA synovium and inflammatory activity of arthritis as well as color flow signals, since the grade of the color flow signals correlated with the grade of synovial effusion as was described in the present study and the previous one.…”
Section: Discussionmentioning
confidence: 52%
“…[1][2][3][4][5] Vascular resistance of the peripheral vessels has been quantitatively demonstrated by pulse-waved spectral Doppler sonography and a decreased resistance of synovial vessels in RA patients has recently been reported, 3,6,7 However, a correlation between increased vascularization and decreased vascular resistance in the inflammatory synovium has not been clearly demonstrated. In the present study, power Doppler and spectral Doppler sonography were used to assess 56 knee joints from 28 RA patients.…”
Section: Introductionmentioning
confidence: 97%
“…Qvistgaard et al 16 found, however, a positive correlation of the intensity of synovial vascularization with ESR but not with CRP. In contrast, Carotti et al 17 and Shahin et al 25 found no correlation between synovial vascularization and the ESR. Such controversial results might be due to differences in such factors as the sites of the joints scanned, activity of other joints, or disease duration.…”
Section: Discussionmentioning
confidence: 89%
“…Increased blood flow on CD or PD may occur with inflammation and neovascularization and is useful in determining the presence of synovitis. However, some sonographers suggest that increased PD signals can be present near the epiphyses of growing bones in healthy children, which may be incorrectly interpreted on MSK-US as synovitis [14]. Another study noted the presence of PD signal in physeal/epiphyseal cartilage in 4.2% of the studied joints in healthy children [15].…”
Section: Technical Aspects Of Msk-usmentioning
confidence: 96%
“…Unlike conventional radiography, an established imaging technique for identifying progressive joint damage, US is sensitive to soft tissue lesions and can detect early erosive bone lesions [1,2]. The development of higher frequency probes (12)(13)(14)(15)(16)(17)(18) and portable US machines has led to better resolution of small joints and the increased use of MSK-US in patients with rheumatologic disease. Improvements in color Doppler (CD) and power Doppler (PD) imaging, where the amount of color is related to degree of blood flow, allow for better assessment of soft tissue inflammation [1,3,4].…”
Section: Reviewmentioning
confidence: 98%